On the Need to Strengthen Social Capital in Pro-Inclusive Education and Supporting People with Disabilities - Janiszewska-Nieścioruk, Zdzisława (Przegląd Badań Edukacyjnych (Educational Studies Review), 2019)
In the article, I point out the weaknesses in the domestic social capital and at the same time I emphasize its key role in creating pro-inclusive actions and solutions for people with disabilities in all spheres or areas of their life activities. However, the subject of my special reflection is the education system and the need to strengthen capital resources and social trust in its space. It is the basis for the inclusion and support of these people and their families in the cooperation with the local environment. It creates a climate for practicing civic skills; readiness of all entities/participants of education for a mutual, based on trust and respect cooperation that is open to the possibility of including others to a different extent and whom are not only formally involved in their education.